TURKEY'S FOREIGN POLICY AT THE PRESENT STAGE: THE MODERNISM OR TRADITIONALISM? - Tatiana Anatolievna Kornienko (Современная наука и инновации, 2022)
The main directions of foreign policy of Turkey are discusses. The relationship of the Republic of Turkey with the European Union, countries of the Middle East, Central Asia, South Caucasus are allocated.